Characteristics and phylogenetic studies of Acrossocheilus parallens (Cypriniformes, Barbinae) complete mitochondrial genome. (1st November 2016) - Han, Chong; Li, Qiang; Xu, Junqiu; Li, Xiufeng; Huang, Jianrong
Abstract: In this paper, the complete mitochondrial genome sequence of Acrossocheilus parallens was determined. The circle genome (16 591 bp) comprises 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and one control region. The overall base composition of A. parallens is 30.9% for A, 28.1% for C, 24.6% for T, and 16.4% for G, with a higher AT content of 55.5%. Only ND6 and other eight tRNA genes are encoded on the L-strand while most of these genes are located in the H-strand. It has the typical vertebrate mitochondrial gene arrangement. The phylogenetic trees showed that A. parallens was clustered with other species of Acrossocheilus. The complete mitochondrial genomic sequence of A. parallens would contribute for the better understanding of genetic structure, identification, evolution and phylogeny of this species.